Functional Foods in Macedonia: Consumers’ Perspective and Public Health Policy - Spiroski, Igor; GJorgjev, Dragan; Milosevic, Jasna; Kendrovski, Vladimir; Naunova-Spiroska, Daniela; Berjolle, Dominique (ID Design 2012/DOOEL Skopje, 2013)
Background: The objective of our study was to explore the knowledge, attitudes and practices of Macedonian consumers towards functional foods, to predict future trends and to assess the national public health policies encompassing the functional foods market. Methods: Total of 518 respondents aged 18+, from all regions in the country participated in the study. They were sampled through three-staged national representative sampling procedures. The questionnaire comprised questions regarding the level of information about functional foods, trust in health claims, frequency of consumption and knowledge and attitudes related to those foods. Statistical significance was determined at p<0.05. Results: Respondents aged 18-34 were more informed compared to the total population (22 and 16 % respectively, p<0.05). Most of the consumers consume these products once a day. Employed consumers were willing to increase daily consumption from 3 to 18 % (p<0.05). On average 65.1% of the statements assessing knowledge were answered correctly. On a scale from -3 to +3 functional foods were considered as very healthy (mean=2.03, SD=1.42). Conclusion: On average, Macedonian consumers have a positive attitude and high expectations of functional foods. Public health policies still lag when compared to comprehensive approach of the food industry in market placement of these products.
Keywords: functional foods; attitudes; consumers; Macedonia; public health